Design of Bird Pest Control Using Arduino Uno Based Sensors on Rice Plants (Oryza sativa L.) - Qurnain, Muhammad Zul; abdus, syakur; Hariati; Sarjan, Muhammad (Journal of Multidisciplinary Science and Natural Resource Management, 2025)
Bird pest control in rice plants (Oryza sativa L.) is a major challenge in agriculture, because birds often damage crops which can cause significant economic losses. This study aims to design and develop a bird pest control system using Arduino Uno-based sensors that can detect the presence of birds and provide a response to repel them automatically. This system consists of an ultrasonic sensor to detect bird movement, then the Buzzer makes a sound and the Servo makes a movement to scare away bird pests. The advantage of this system is its ability to be integrated with Internet of Things (IoT) technology, which allows farmers to monitor and control the bird repellent system remotely via a smartphone application. Thus, this research is expected to contribute to the development of smarter and more sustainable agricultural technology, as well as reduce dependence on more environmentally damaging pest control methods. The implementation of this Arduino-based system is expected to be an effective alternative solution in controlling bird pests in rice plants, while opening up opportunities for further innovation in the field of technology-based agriculture.